MRI-detection rate and incidence of lumbar bleeding sources in 190 patients with non-aneurysmal SAH - Kashefiolasl, Sepide (PLoS One, 2017)
BACKGROUND: Up to 15% of all spontaneous subarachnoid hemorrhages (SAH) have a non-aneurysmal SAH (NASAH). The evaluation of SAH patients with negative digital subtraction angiography (DSA) is sometimes a diagnostic challenge. Our goal in this study was to reassess the yield of standard MR-imaging of the complete spinal axis to rule out spinal bleeding sources in patients with NASAH. METHODS: We retrospectively analyzed the spinal MRI findings in 190 patients with spontaneous NASAH, containing perimesencephalic (PM) and non-perimesencephalic (NPM) SAH, diagnosed by computer tomography (CT) and/or lumbar puncture (LP), and negative 2nd DSA. RESULTS: 190 NASAH patients were included in the study, divided into PM-SAH (n = 87; 46%) and NPM-SAH (n = 103; 54%). Overall, 23 (22%) patients had a CT negative SAH, diagnosed by positive LP. MR-imaging of the spinal axis detected two patients with lumbar ependymoma (n = 2; 1,05%). Both patients complained of radicular sciatic pain. The detection rate raised up to 25%, if only patients with radicular sciatic pain received an MRI. CONCLUSION: Routine radiological investigation of the complete spinal axis in NASAH patients is expensive and can not be recommended for standard procedure. However, patients with clinical signs of low-back/sciatic pain should be worked up for a spinal pathology.